SCREENING OF PREGNANT WOMEN FOR GESTATIONAL DIABETES MELLITUS - Hassan, Aisha (Journal of Ayub Medical College Abbottabad, 2005)
Background: Gestational diabetes mellitus is associated with significant fetal and neonatal morbidity and mortality. It is a definitive risk factor for the future development of type - II diabetes mellitus in the mother. Our objective was to evaluate the effectiveness of screening by 50gm oral glucose challenge test to detect the gestational diabetes mellitus and impaired glucose tolerance in pregnant women. Methods: This study was conducted in the Department of Gynaecology at Lady Reading Hospital, Peshawar. A total of 1000 women were screened in antenatal clinic by giving them 50 gm oral glucose solution and estimation of plasma glucose level 1 hour after glucose intake. Those with plasma glucose in excess of 130mg/dl (cut off value for screen positive) were subjected to 3 hours oral glucose tolerance test to confirm the diagnosis of gestational diabetes mellitus. Result: Out of 1000 cases tested, 43 were found to have Gestational Diabetes Mellitus and 17 cases had impaired glucose tolerance. The mean age of the patients ranged between 21 and 42 years. Most of the positive patients carried medical and obstetric historic risk factors for diabetes mellitus like obesity, advanced age and parity and bad obstetric history. They also had associated complications of gestational diabetes mellitus like pre eclampsia and polyhydramnios in current pregnancy. Also more than 80% of the patients had family history of risk factors like diabetics mellitus obesity, hypertension etc. Conclusions: 50gm Oral Glucose Challenge Test can be used in pregnant ladies from 24 weeks onward to detect the common disorders of Gestational Diabetes Mellitus and Impaired Glucose Tolerance. Key Words: Gestational Diabetes Mellitus, Impaired Glucose Tolerance, Oral Glucose Challenge Test, Full Oral Glucose Tolerance test